EU policies on Huawei and 5G wireless networks : economic-technological opportunities vs cybersecurity risks - Umbach, Frank (Nanyang Technological University, 2021)
gainst the backdrop of the global US–China–EU technology competition, this working paper examines the security–economic nexus as European policymakers prepare for the rollout of the next-generation mobile technology network or 5G. Using a comparative approach, it will explore how various EU institutions and EU members approach the tradeoffs between their technological and economic–industrial policies and the inherent cybersecurity risks in 5G technology, notably, the risks in the prospective involvement of the Chinese company Huawei in their 5G rollout. It will particularly look at the approaches of the United Kingdom, Germany and France. The key question that will be addressed is whether the UK government’s turnaround in July 2020 to ban Huawei from its 5G rollout and the increasingly assertive stance of several EU member states against Huawei and China are merely the result of American political pressure or the consequence of the changing EU–China relationship or both.